Prevalence of Tertiary Level Students’ Critical Thinking Skills in Speaking - Anjaniputra, Agung Ginanjar (International Journal of Education, 2020)
Critical thinking is deemed vital to students’ success of learning. Not only does it help in processing information received through written and oral communication, but also it enhances the quality of language which is produced logically and reasonably. Critically thinking of what to say has been deemed intricate and more demanding by most students. Thus, this study is intended to investigate critical thinking of students at tertiary level, particularly critical thinking aspects demonstrated in speaking. To address this issue, this study deploys a case study qualitative design to gain in-depth, thorough, comprehensive understanding. Involving the second year university students, this study results in findings that some aspects of critical thinking are demonstrated by the students in their speaking performance, encompassing relevance, clarity, consistency, accuracy and fairness, and that trends of how these aspects of critical thinking occurs, entailing deductive and inductive reasoning, cause and effect, comparison, planning as well as hypothesizing, are interpreted and discussed. Therefore, critical thinking is necessary and this needs improvement if students’ success in the new world era is to be attained.